2014
DOI: 10.1371/journal.pone.0110442
|View full text |Cite
|
Sign up to set email alerts
|

Transcription of Hepatitis B Virus Covalently Closed Circular DNA Is Regulated by CpG Methylation during Chronic Infection

Abstract: The persistence of hepatitis B virus (HBV) infection is maintained by the nuclear viral covalently closed circular DNA (cccDNA), which serves as transcription template for viral mRNAs. Previous studies suggested that cccDNA contains methylation-prone CpG islands, and that the minichromosome structure of cccDNA is epigenetically regulated by DNA methylation. However, the regulatory effect of each CpG island methylation on cccDNA activity remains elusive. In the present study, we analyzed the distribution of CpG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
91
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 80 publications
(93 citation statements)
references
References 44 publications
(68 reference statements)
0
91
0
2
Order By: Relevance
“…The presence of Cp on CpG island 2 correlates with increased activity of cccDNA (i.e. viral load), while methylation of DNA in CpG islands 2 and 3 correlates with decreased cccDNA activity (Guo et al, 2011; Zhang et al, 2014). Of note, small molecules that drive Cp assembly (Bourne et al, 2008), presumably depleting the concentration of free Cp, led to depletion of cccDNA-bound Cp and decreased production of viral RNA and proteins (Belloni et al, 2013).…”
Section: Cp and Cccdnamentioning
confidence: 99%
“…The presence of Cp on CpG island 2 correlates with increased activity of cccDNA (i.e. viral load), while methylation of DNA in CpG islands 2 and 3 correlates with decreased cccDNA activity (Guo et al, 2011; Zhang et al, 2014). Of note, small molecules that drive Cp assembly (Bourne et al, 2008), presumably depleting the concentration of free Cp, led to depletion of cccDNA-bound Cp and decreased production of viral RNA and proteins (Belloni et al, 2013).…”
Section: Cp and Cccdnamentioning
confidence: 99%
“…The CpG islands were defined based on the following criteria: a GC content of Ն50%, an observed-to-expected CpG dinucleotide ratio of Ն0.60, and a sequence window longer than 100 bp. Bisulfite sequencing primers were designed separately for both CpG islands II (nt 1228 to 1663) and III (nt 2295 to 2446) to avoid overlap between CpG sites (Table 1) (32). DNA samples were modified using the Cells-to-CpG bisulfite conversion kit (Applied Biosystems) according to the manufacturer's specifications.…”
Section: Methodsmentioning
confidence: 99%
“…Island I contains the start site of the S gene, island II spans a region that overlaps enhancer I/II and is proximal to the core promoter, and island III covers the start codon of the polymerase gene and the upstream region of the SP1 promoter (32,33). It was reported that transcription of HBV cccDNA is regulated by CpG methylation during chronic infection (27,33).…”
Section: Persistent Loss Of Serum Hbv Markers In Micementioning
confidence: 99%
“…In the HBV-infected liver, free HBV DNA and its products are causally related to the activity of liver disease, but the persistence of HBV infection is maintained by the nuclear cccDNA, which serves as a transcription template for HBV mRNA [111,112] . Although there are several opposing views [113] , it was reported that HBV cccDNA is noncytolytically degraded by agents that upregulate apolipoprotein B mRNA editing enzyme and catalytic polypeptide-like (APOBEC) 3A and 3B [23] .…”
Section: Treatment For Hbv Cccdnamentioning
confidence: 99%